Religion as a Human Right and a Security ThreatInvestigating Young Adults' Experiences of Religion in Finland - Niemi, Pia-Maria; Kallioniemi, Arto; Ghosh, Ratna (2019)
The emergence of religiously motivated terrorist attacks and the increasing xenophobia expressed in Europe concern religions in many ways. Questions related to religion also lie at the core of educational aims and practices used to create national cohesion and understanding about different types of values and worldviews. However, despite the topicality of the issue, we have little knowledge about the ways in which young adults experience religions in a secular state. In order to contribute to the discussion regarding the relationships between religion, nationality, security, and education, this study focuses on investigating how politically active young adults experience the role of religions in Finnish society. The qualitative data of this study were collected from young adults (18-30-year-olds) through an online questionnaire distributed through political youth organisations. The content analysis of the responses (altogether 250 respondents) identified five main orientations towards religions. The findings highlight the importance of providing young people with education about different faiths and worldviews for reducing prejudices, especially those related to Islam. The findings also highlight the need to address in education and society the possible but not as self-evident relationship between violence and religion, and to do this more explicitly than is currently done.
Keywords: Education; Nationalism; Religion; Security; Terrorism